Quantitative chemical proteomics profiling of de novo protein synthesis during starvation-mediated autophagy. Issue 10 (2nd October 2016) - Wang, Jigang; Zhang, Jianbin; Lee, Yew-Mun; Koh, Pin-Lang; Ng, Shukie; Bao, Feichao; Lin, Qingsong; Shen, Han-Ming
ABSTRACT: Autophagy is an intracellular degradation mechanism in response to nutrient starvation. Via autophagy, some nonessential cellular constituents are degraded in a lysosome-dependent manner to generate biomolecules that can be utilized for maintaining the metabolic homeostasis. Although it is known that under starvation the global protein synthesis is significantly reduced mainly due to suppression of MTOR (mechanistic target of rapamycin serine/threonine kinase), emerging evidence demonstrates that de novo protein synthesis is involved in the autophagic process. However, characterizing these de novo proteins has been an issue with current techniques. Here, we developed a novel method to identify newly synthesized proteins during starvation-mediated autophagy by combining bio-orthogonal noncanonical amino acid tagging (BONCAT) and isobaric tags for relative and absolute quantitation (iTRAQ TM ). Using bio-orthogonal metabolic tagging, L-azidohomoalanine (AHA) was incorporated into newly synthesized proteins which were then enriched with avidin beads after a click reaction between alkyne-bearing biotin and AHA's bio-orthogonal azide moiety. The enriched proteins were subjected to iTRAQ labeling for protein identification and quantification using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Via the above approach, we identified and quantified a total of 1176 proteins and among them 711 proteins were found to meet our defined criteria as de novo synthesized proteins during starvation-mediated autophagy. The characterized functional profiles of the 711 newly synthesized proteins by bioinformatics analysis suggest their roles in ensuring the prosurvival outcome of autophagy. Finally, we performed validation assays for some selected proteins and found that knockdown of some genes has a significant impact on starvation-induced autophagy. Thus, we think that the BONCAT-iTRAQ approach is effective in the identification of newly synthesized proteins and provides useful insights to the molecular mechanisms and biological functions of autophagy.